Музейні установи в українському національному русі Наддніпрянщини наприкінці ХІХ - на початку ХХ ст. - Дворкін, І. (Місто: історія, культура, суспільство, 2017)
У статті розглядається місце музеїв та музейної справи в діяльності українського національного руху наприкінці ХІХ – на початку ХХ ст. Музейні установи давали можливість представникам української творчої інтелігенції, українофілам легальним способом поширювати ідею «українського проекту». Це відбувалось в умовах відсутності власної держави та російської імперської політики, що заперечувала існування окремого українського народу. Музейні установи імперського періоду за явним чи прихованим задумом їхніх засновників мали потенціал стати українськими національними. Реалізація таких музейних проектів представлена у статті на прикладі Київського художньо-промислового та наукового музею та Музею українських старожитностей В.В. Тарновського. The article deals with the place of museums and museum affairs in the Ukrainian national movement activity in the late XIX and early XX century. The Museum institutions enabled the representatives of the Ukrainian intellectuals, Ukrainophiles the legal way to spread the «Ukrainian project» idea. This happened in the absence of their own state and Russian imperial policy that denied the existence of a separate Ukrainian nation. The question of the imperial authorities influence to the development of museums and the control of Ukrainophiles activities is analyzed. Officially authorized by imperial power institutions, including museums, provided Ukrainophile’s wide opportunities. The imperial period museum institution by explicit or implicit intention of their founders had the potential to become a Ukrainian national museums. The implementation of museum projects is presented in the article on the Kyiv Art, Industry and Science Museum and the Museum of Ukrainian Antiquities example. The article discusses the museum exhibitions and excursions impact to perception of historical events by public.